Peran Orang Tua Dalam Menjaga Kebersihan Gigi Dan Mulut Pada Anak Usia Balita Di Desa Variagung - Rahmanto, Arif (Wellness And Healthy Magazine, 2021)
Introduction: Children's dental health is of particular concern in today's modern era. Children under five generally do not know and have not been able to maintain the health of their oral cavity, so parents are responsible for educating them properly. Parental knowledge is very important in underlying the formation of behaviour that supports or does not support children's dental and oral hygiene. Many parents assume that deciduous teeth are only temporary and will be replaced by permanent teeth, so they do not pay attention to the child's dental hygiene. When in fact during the milk teeth that children should begin to be taught to maintain the cleanliness and health of their teeth. Method: This literature review uses a critical review of full-text articles in the last ten years, from 2010-2020 in Indonesian and English. Because of the limitations of the article, quantitative studies are used to obtain a more accurate review. Google Scholar database search, National Library of the Republic of Indonesia, PubMed, Proquest with the keywords “Role of Parents”, “Dental and Oral Hygiene”, “Toddler” to get articles that match the topic and purpose. 17 articles in Google Scholar, Then the article is read intensively, and a summary of each article is made. Results: Mother's knowledge in health care had a significant influence on children's attitudes and behaviours in maintaining oral and dental hygiene. This can be seen from the habits of parents who always give sweet food to their children, as well as the knowledge of parents who do not know about the effects of not maintaining dental and oral hygiene in toddlers. Conclusion: Dental health education should be introduced as early as possible to children so they can know how to maintain their dental health and it is hoped that parents will also play a role in supervising the dental hygiene of their children by teaching them how to brush their teeth properly.